Effect of Differentiated Phonics Instructional Strategy on Primary School Pupil’s Learning Outcomes in English Literacy Skills in Ikere - Ekiti - Alonge, Sunday; Obadare, F. T.; Obateru, O. T. (NIU Journal of Humanities; Vol 2 No 1 (2017): KIU Journal of Humanities, Vol. 2 No. 1, June 2017, 2017)
The study examined the effect of differentiated phonics instructional strategy on primary school pupils’ leaning outcomes in English literacy skills in Ikere Ekiti metropolis. One hundred and twenty (120) pupils were sampled and participated in English Language achievement test. The study adopted an experimental research design. The study revealed that differentiated phonics instructional strategy has an effect on pupils literacy skills, it was therefore recommended that effective use of differentiated phonics instructional strategy should be adopted in teaching and learning of literacy skills. Keywords: Differentiated Phonics, Instructional Strategy